2023
DOI: 10.1038/s41467-023-37671-x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial FAT1 inhibits angiogenesis by controlling YAP/TAZ protein degradation via E3 ligase MIB2

Abstract: Activation of endothelial YAP/TAZ signaling is crucial for physiological and pathological angiogenesis. The mechanisms of endothelial YAP/TAZ regulation are, however, incompletely understood. Here we report that the protocadherin FAT1 acts as a critical upstream regulator of endothelial YAP/TAZ which limits the activity of these transcriptional cofactors during developmental and tumor angiogenesis by promoting their degradation. We show that loss of endothelial FAT1 results in increased endothelial cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…A few resistance pathways that affect CDK4/6 activity include FAT1, YAP/TAZ, and TP53. 38,39 In previous studies, the loss of FAT1 tumor suppressor promotes resistance to CDK4/6 inhibitors via the Hippo pathway, which regulates transcriptional coactivators. 39 A summary of the FAT1 resistance pathway and components of the Hippo signaling pathway is found in Figure 2.…”
Section: Resistance Pathways Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…A few resistance pathways that affect CDK4/6 activity include FAT1, YAP/TAZ, and TP53. 38,39 In previous studies, the loss of FAT1 tumor suppressor promotes resistance to CDK4/6 inhibitors via the Hippo pathway, which regulates transcriptional coactivators. 39 A summary of the FAT1 resistance pathway and components of the Hippo signaling pathway is found in Figure 2.…”
Section: Resistance Pathways Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…38,39 In previous studies, the loss of FAT1 tumor suppressor promotes resistance to CDK4/6 inhibitors via the Hippo pathway, which regulates transcriptional coactivators. 39 A summary of the FAT1 resistance pathway and components of the Hippo signaling pathway is found in Figure 2. A study by Li et al, revealed that FAT1 loss led to CDK6 overexpression and increased minimum inhibitory concentration of CDK4/6 inhibitors by 4 to 6 folds.…”
Section: Resistance Pathways Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, neovascularization in tumors is a highly complicated process. Besides sprouting angiogenesis, many other vascularization mechanisms, such as endothelial progenitor cell (EPC) recruitment, vascular co-option, intussusceptive angiogenesis, and VM, have been discovered in tumors (Li et al 2023 ; Ayala-Dominguez et al 2019 ). VM represents a tumor microcirculation model that refers to the formation of non-endothelial blood vessels by tumor cells through extracellular matrix remodeling and deformation (Fernandez-Cortes et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%